Sex differences in response to lifestyle intervention among children and adolescents: Systematic review and meta‐analysis. Issue 3 (10th February 2023) - Mast, Alexis; Peña, Armando; Bolch, Charlotte A.; Shaibi, Gabriel; Vander Wyst, Kiley B.
Abstract: Objective: Little is known about sex differences in response to lifestyle interventions among pediatric populations. The purpose of this analysis was to evaluate sex differences in adiposity following lifestyle interventions among children and adolescents with overweight or obesity aged 6 to 18 years old. Methods: Searches were conducted in PubMed, Web of Science, and MEDLINE (from inception to March 2021), and references from included articles were examined. Eligibility criteria included children and adolescents aged 6 to 18 years with overweight or obesity, randomization to a lifestyle intervention versus a control group, and assessment of at least one adiposity measure. Corresponding authors were contacted to obtain summary statistics by sex ( n  = 14/49). Results: Of 89 full‐text articles reviewed, 49 (55%) were included, of which 33 (67%) reported statistically significant intervention effects on adiposity. Only two studies (4%) evaluated sex differences in response to lifestyle intervention, reporting conflicting results. The results of the meta‐regression models demonstrated no significant differences in the treatment effect between male and female youth for weight (beta = −0.05, SE = 0.18, z  = −0.28, p  = 0.8), BMI (beta = 0.03, SE = 0.14, z  = 0.19, p  = 0.85), BMI z score (beta = −0.04, SE = 0.18, z  = −0.23, p  = 0.82), percentage body fat (beta = −0.11, SE = 0.16, z  = −0.67, p  = 0.51), and waist circumference (beta = −0.30, SE = 0.25, z  = −1.18, p  = 0.24). Conclusions: The meta‐analysis revealed that youth with overweight or obesity do not demonstrate a differential response to lifestyle intervention in relation to adiposity‐related outcomes.